Dag Hammarskjöld, the “epochè” of solitary meditation - Cesarone, Virgilio (Razón y fe, 2025)
Dag Hammarskjöld, UN Secretary General who died in 1961, tried to work towards a conciliation for peace by virtue of personal isolation through a suspension of specific political militancy. The intention of this contribution is to allow the “political” virtue of the epochè to emerge, as it can be understood from his written legacy, and consequently his political action. The parallelism between the phenomenological attitude and that proper to Hammarskjöld’s meditations must be stripped of all the gnoseological peculiarities belonging to the modern subject. If, in fact, the epochè of Husserlian is a return of all the primordial contents of consciousness to an identical subject of knowledge, in Hammarskjöld, the ‘subject’ is the one who seeks the originality of giving oneself to consciousness in listening to one’s own freedom, which is not the arbitrariness of the ability to “do”, but the attention, with respect to what the world offers us.
Keywords: political theology; epochè; inner stillness; meditation; responsibility; religion